Go Cap Lak : Ritual dan Identitas Baru Etnis Tionghoa di Bagansiapiapi - Zuli Laily Ianaini (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2012)
His paper aims to describe the ritual fuel Barge Chinese society into anew cultural identy for people of Chinese descent in Bagansiapapi. Fuci barges or known by the name of Go Cap Lak Bagansiapiapi only found in the district and conducted annually by the people of Chinese descent.Go Cap Lak ceremony is an annual ritual held by the Chinese community in Bagansiapiapi the fifth month (Go) Imlek on the sixteenth (Cap Lak) as an expression of gratitude and thanks to the God of the Sea Gods Kie Ong Ya have provided prosperty and health. Go Cap Lak ceremony fuel barge is present only in Bagansiapiapi and serve as icons of cultural identity or to attract tourists. The development of this program is to increase the diversity of economic and social life in the city Bagansiapiapi. Ritual Go Cap Lark or fuel barge into a new identity for a long time Bagansiapapi and shifting identity as a city of the world’s number two producer of fish in the middle of the 20 th century into a tourist city.